1999
DOI: 10.1046/j.1464-410x.1999.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum prostate specific antigen levels in conjunction with an initial prostatic biopsy negative for carcinoma: who should undergo a repeat biopsy?

Abstract: Objective To determine the outcome of repeated prostatic biopsies in men attending with suspected prostate cancer but an initial negative biopsy. Patients and methods Patients who had undergone two or more transrectal ultrasonography (TRUS)‐guided prostate biopsies were identified from the Hospital Information Support System database. Indications for TRUS were a raised prostate‐specific antigen (PSA) level (>4.0 ng/mL), with or without an abnormal digital rectal examination (DRE). Sextant prostate biopsies plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…BHP is the enlargement of the prostate gland by increased tissue mass in the transition zone of the prostate, a prevalent, chronic and progressive disease (87). Preliminary works reported that 11-44% of BHP progressed to PCa within 7 years (88)(89)(90). HPV infection was also identified in the BHP tissue samples of the included studies.…”
Section: Discussionmentioning
confidence: 96%
“…BHP is the enlargement of the prostate gland by increased tissue mass in the transition zone of the prostate, a prevalent, chronic and progressive disease (87). Preliminary works reported that 11-44% of BHP progressed to PCa within 7 years (88)(89)(90). HPV infection was also identified in the BHP tissue samples of the included studies.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple needle cores are obtained randomly within targeted areas of the prostate gland, since tumour foci are too small to be visualized. Despite the multiple samplings, areas of cancer may be missed by the biopsy procedure and the false negative rate has ranged from 10% to 30% (Rietbergen et al 1998; Durkan & Greene 1999). The practice of conducting a repeat biopsy after an initial negative biopsy is variable and not well established due to the lack of definitive predictor variables that can identify patients at high risk for having prostate cancer (Djavan et al 2000; Roehl et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 33 % of patients were diagnosed with prostate cancer in the initial biopsy and 26.3 % of the patients were diagnosed with prostate cancer after a repeat prostate biopsy. Because of the possibility of failure in the initial biopsy and the possibility of detection of prostate cancer in a repeat biopsy, repeat prostate biopsy is considered to be necessary for many patients [11,12]. Indications for repeat prostate biopsy include rising or persistent PSA levels, suspicious DRE results, atypical small acinar proliferation, and extensive high-grade prostatic intraepithelial neoplasia (i.e., in multiple biopsy sites) [13].…”
Section: Discussionmentioning
confidence: 99%